Pendampingan Pembuatan Pakan Ternak dari Limbah Pembungkus Lontong untuk Peningkatan Ekonomi Masyarakat di Kelurahan Kupang Krajan Kecamatan Sawahan Kota Surabaya - Wiwik Handayani; Sri suryani Yuprapti Winasih; Sinta Dewi; Badi’ah Badi’ah (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2020)
Banana leaf waste in kupang krajan village is very abundant. This becomes a problem of garbage buildup. Therefore, it is necessary to process waste in order to become a useful product. By using assed based community development (ABCD) method aims to provide training in making animal feed from banana leaf waste. The results of the training showed that the people of Kupang Krajan village were able to make quality animal feed with a fragrant aroma. Animal feed has also been tested to beef cattle, dairy cows, and goats in west Surabaya and Gresik. There are cattle that eat directly and some still have to adapt.